Measuring volatility linkage, clustering and sensitivity to external shocks in Nigerian stock index. (23rd September 2019) - Abdullahi, Shafiu Ibrahim
Recent events in the global economy have further exposed the fear and uneasiness in the minds of investors around the world. The resort to protectionist policies by nations around the world as reaction to the attempt by US President Donald Trump to use higher tariffs to increase his country's share of global trade has made global investors seek safe havens. This paper measures stock market volatility and linkages among three stock markets. EGARCH and TGARCH models were employed in analysing univariate volatility in the indices, while bivariate GARCH (diagonal BEKK) was employed in measuring returns linkages. The result of the analysis shows that markets exhibit evidence of asymmetry and persistence in volatility; volatility from previous periods significantly affects current period and markets react with speed to news of volatility. In terms of portfolio diversification, NSE-IST provides better opportunity followed by NSE-JSE and then JSE-IST.